The Effect of Interval Training on Increasing VO2. Max in Pencak Silat Athletes Fostered by ASBD Bengkulu - Nofriyantoni; Dian Pujianto; Ari Sutisyana (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
Background: This study aims to determine the effect of Interval Training on VO₂Max ability in pencak silat athletes fostered by Al-Azhar Martial Arts Bengkulu Branch. Improving VO₂Max is essential for achieving optimal performance, especially in endurance-demanding martial arts such as pencak silat. Methods: This research employed a pre-experimental design with one group pretest–posttest. The population consisted of pencak silat athletes fostered by the Al-Azhar Martial Arts Bengkulu Branch, and 26 pre-teen athletes were selected as the sample. Data were collected using the Multistage Fitness Test. Statistical analysis included normality test, homogeneity test, and paired t-test. Result: The findings revealed that the calculated t-value (11.38) was greater than the t-table value (1.708) at a significance level of α = 0.05, indicating a significant effect. After 16 training sessions, the VO₂Max of athletes increased by 22.58%. Conclusion: Interval Training significantly improves VO₂Max ability in pencak silat athletes fostered by Al-Azhar Martial Arts Bengkulu Branch. Therefore, interval training can be considered an effective program to enhance aerobic endurance and support athletic performance in pencak silat.